Fundamentals of rice crop science - Yoshida, Shouichi,Yoshida, Shouichi (IRRI, 1981)
The book presents a synthesis of the current understanding of rice crop physiology. It explains how high rice yields can be archived with the proper combination of variety, environment, and cultural practices. It also presents some means to identify the cause of low and high yields under a given crop environment